2014
DOI: 10.6023/a14030233
|View full text |Cite
|
Sign up to set email alerts
|

Solvo/Hydrothermal Preparation of MnOx@rGO Nanocomposites for Electrocatalytic Oxygen Reduction

Abstract: and MnOOH. Among the tested samples, MnOOH@rGO exhibited superior ORR activity with a onset-potential of -0.11 V, a half-wave potential of -0.32 V and a high kinetic limiting current density (J k ) of 4.69 mA·cm -2 at -0.6 V. Furthermore, MnOOH@rGO enabled an apparent 4-electron reduction of oxygen and showed considerable durability. The superior performance of MnOOH@rGO hybrid was attributed to the synergistic effect of rGO substrate and MnOOH nanorods and indicated its promising application as efficient ORR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…19 Transition metal oxides (such as manganese oxides) represent another class of oxygen electrocatalysts for their advantages of low cost, high abundance, environmentally benign and considerable catalytic activity in both aqueous and aprotic electrolytes. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Recently, we have revealed that composite manganese oxides (i.e., CaMnO 3 ) exhibit enhanced ORR/OER activity in comparison with binary manganese oxides. [36][37][38][39] Aiming at exploring efficient cathode catalysts composed of earth-abundant and inexpensive elements for rechargeable Na-O 2 technologies, it deserves special attention to make use of metal oxides in this emerging battery chemistry.…”
mentioning
confidence: 99%
“…19 Transition metal oxides (such as manganese oxides) represent another class of oxygen electrocatalysts for their advantages of low cost, high abundance, environmentally benign and considerable catalytic activity in both aqueous and aprotic electrolytes. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Recently, we have revealed that composite manganese oxides (i.e., CaMnO 3 ) exhibit enhanced ORR/OER activity in comparison with binary manganese oxides. [36][37][38][39] Aiming at exploring efficient cathode catalysts composed of earth-abundant and inexpensive elements for rechargeable Na-O 2 technologies, it deserves special attention to make use of metal oxides in this emerging battery chemistry.…”
mentioning
confidence: 99%
“…Li-O 2 电池与锂离子电池在电池结构 和组成上具有相似性(如: 金属锂负极、有机电解液、隔 膜). 金属氧化物不仅是锂离子电池正极活性物质, 也 是理想的氧还原氧析出电催化材料, 可应用于 Li-O 2 电 池空气正极 [20] . 因此, 将废旧的锂离子电池作为 [21] .…”
Section: 引言unclassified
“…Even though the amount of Pt needed to achieve the desired catalytic effect can now be reduced by using Pt alloys [14,15] or making core-shell structures with supporting materials [16], the commercial scale-up of production at low cost remains challenging. In this context, much recent effort has been devoted to developing alternative ORR electrocatalysts, including molecular electrocatalysts [5,[17][18][19], metal-nanomaterial-based electrocatalysts [20][21][22][23][24][25], metal-oxide-based electrocatalysts [2,26] and newly emerging two-dimensional electrocatalysts [27][28][29][30]. Although a few outstanding review papers have been published in the field of ORR electrocatalysts recently [2,3,6,12,[21][22][23], a comprehensive coverage of various facets, particularly those investigated in the past 10 years, is still lacking.…”
Section: Introductionmentioning
confidence: 99%